Fluid and solute transport by cells and a model of systemic circulation. - Yufei Wu; Morgan A Benson; Sean X Sun (PLoS Computational Biology)
Active fluid circulation and solute transport are essential functions of living organisms, enabling the efficient delivery of oxygen and nutrients to various physiological compartments. Since fluid circulation occurs in a network, the systemic flux and pressure are not simple outcomes of individual components. Rather, they are emergent properties of network elements and network topology. Moreover, consistent pressure and osmolarity gradients are maintained across compartments such as the kidney, interstitium, and blood vessels. The mechanisms by which these gradients and network properties are established and maintained are unanswered questions in systems physiology. Previous studies have shown that epithelial cells are fluid pumps and can actively generate pressure and osmolarity gradients. The polarization and activity of solute transporters in epithelial cells, which drive fluid flux, are influenced by pressure and osmolarity gradients. Therefore, there is an unexplored coupling between pressure and osmolarity in the circulatory network. In this work, we develop a mathematical framework that integrates the influence of pressure and osmolarity on solute transport. We use this model to explore both cellular fluid transport and systemic circulation. Using a simple network featuring the kidney-vascular interface, we show that our model naturally generates pressure and osmolarity gradients across the kidney, vessels and renal interstitium. While the current model uses this interface as an example, the findings can be generalized to other physiological compartments. This model demonstrates how systemic transport properties can depend on cellular properties and, conversely, how cell states are influenced by systemic properties. When epithelial and endothelial pumps are considered together, we predict how pressures at various points in the network depend on the overall osmolarity of the system. The model can be improved by including physiological geometries and expanding solute species, and highlights the interplay of fluid properties with cell function in living organisms.